2001
DOI: 10.1210/endo.142.3.8032
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Receptors in Thymic Epithelium Modulate Thymus Size and Thymocyte Development*

Abstract: Castration of normal male rodents results in significant enlargement of the thymus, and androgen replacement reverses these changes. Androgen-resistant testicular feminization (Tfm) mice also show significant thymus enlargement, which suggests that these changes are mediated by the androgen receptor (AR). The cellular targets of androgen action in the thymus are not known, but may include the lymphoid cells (thymocytes) as well as nonlymphoid epithelial cells, both of which have been believed to express AR. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
103
0
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(112 citation statements)
references
References 37 publications
5
103
0
4
Order By: Relevance
“…Among these steroids, glucocorticoidinduced thymocyte apoptosis is well established (Nordeen et al 1976;McConkey et al 1989;Petit et al 1995;Mann et al 2000;Wiegers et al 2001). Glucocorticoids are known to play a physiological role during thymocyte selection and thymocyte maturation (Vacchio et al 1998), and a pathological role under stress conditions (Cohen 1992;Olsen et al 2001;Zacharchuk et al 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Among these steroids, glucocorticoidinduced thymocyte apoptosis is well established (Nordeen et al 1976;McConkey et al 1989;Petit et al 1995;Mann et al 2000;Wiegers et al 2001). Glucocorticoids are known to play a physiological role during thymocyte selection and thymocyte maturation (Vacchio et al 1998), and a pathological role under stress conditions (Cohen 1992;Olsen et al 2001;Zacharchuk et al 1991).…”
Section: Introductionmentioning
confidence: 99%
“…These studies showed that thymic epithelial cells express estrogen receptor (ER) and androgen receptor (AR) and that expression of these hormone receptors in the stromal compartment is required for altering bone marrow-derived T cell subsets in the thymus (5,6). In this issue, Dragin et al confirm that sex hormones indeed act on receptors on thymic stromal cells to impinge upon T cell development within the thymus.…”
mentioning
confidence: 98%
“…Early clues that sex hormones may also modulate thymic stromal populations, such as mTECs, came from elegant studies that utilized bone marrow chimeras (5,6). These studies showed that thymic epithelial cells express estrogen receptor (ER) and androgen receptor (AR) and that expression of these hormone receptors in the stromal compartment is required for altering bone marrow-derived T cell subsets in the thymus (5,6).…”
mentioning
confidence: 99%
“…Presumably, the hormone modifies activity of bone marrow polypotent stem cells, stimulates proliferation and migration of these cells, and promotes their differentiation towards erythropoiesis pathway to the detriment of lymphopoiesis, which probably underlies the immunosuppressive effect of testosterone. Along with glucocorticoid, estrogen, and progesterone receptors, thymocytes express receptors for androgens and neurotransmitters, which confirm close relationship between the immune, nervous, and endocrine systems [6,8,9].…”
mentioning
confidence: 96%